ANALISIS RISIKO PRODUKSI USAHATANI PADI SAWAH DI KECAMATAN ANJATAN, KABUPATEN INDRAMAYU - Prasetyo, Kunandar; Utami, Dewanti Risa; Cordanis, Astried Priscilla (Universitas Islam Madura, 2024)
Rice farming is one of the agricultural enterprises with a relatively high production risk. This production risk can lead to decreased production and even crop failure. This study aims to analyze the factors affecting the rice production and analyze the factors affecting production risk in rice farming in Anjatan Subdistrict, Indramayu. This research was conducted in Anjatan Subdistrict, Indramayu Regency. The research location was chosen purposively considering that Anjatan Subdistrict is one of the rice production centers in Indramayu Regency. The sampling method used was a simple random sampling method with a sample size of 50 rice farmers. The data analysis used in this study consisted of rice production risk function analysis and rice production function analysis. The production function used was the Just and Pope production model. The results of the estimation of the production function showed that the seed, fertilizer, labor, and pesticide variables had a significant effect on rice production in Anjatan Subdistrict. Furthermore, the results of the analysis of the rice production risk function showed that seeds and labor are production factors that can reduce production risk (risk-reducing factors), while urea fertilizer and fertilizer are inputs that can increase rice production risk (risk-increasing factors). The results of the analysis on the production and risk production functions show that seeds are an input that significantly increases rice production and can reduce production risk. Increasing the use of seeds, especially superior seeds, can be one of the strategies to increase production and reduce the risk of crop failure.